From On-Air Rebelliousness to the Cult of Positivity: Mediated Identities and Technological Change in Pump Up the Volume (1990) and Eighth Grade (2018) - Andrea Sofía Regueira Martín (Revista Alicantina de Estudios Ingleses)
Thanks to technological change, the negotiation of adolescent identities largely takes part in virtual spaces. Mostly lacking parental supervision, virtual spaces become one of the few arenas where teenagers have unrestricted freedom to perform and construct their identities. Teenage films have depicted the possibilities and dangers of adolescents using technology since personal computers became commonplace in the 1980s. This paper analyses the representation of the relationship between networked virtual spaces and teenage identities in Pump Up the Volume (Allan Moyle, 1990) and Eighth Grade (Bo Burnham, 2018), two teen films in which the use of technology and virtual spaces as a means for self-expression becomes key in the protagonists’ process of identity formation. The generational distance between the two films provides insight not only into technological change, but also into shifting social expectations. While Eighth Grade shows a world in which social media use is commonplace and having a social media profile is expected, Pump Up the Volume depicts a pre-internet world in which social media—in this case amateur radio—is produced and consumed by those whose voices and views are not typically represented or heard. As a consequence, although both films reflect on the relationship between adolescent identities and their performances on social media, they place an emphasis on different aspects of social networks that are specific to each film’s socio-historical context. While Pump Up the Volume presents social media as a tool for rebellion, connection and potential systemic change, Eighth Grade reflects an individualised world in which conformity to neoliberal values—and, more specifically, neoliberal girlhood—replaces rebellion.